Nano-La2O3 Induces Honeybee (Apis mellifera) Death and Enriches for Pathogens in Honeybee Gut Bacterial Communities - Liu, Yong-Jun; Jing, Zhongwang; Bai, Xue-Ting; Diao, Qing-Yun; Wang, Jichen; Wu, Yan-Yan; Zhao, Qing; Xia, Tian; Xing, Baoshan; Holden, Patricia A.; Ge, Yuan (Frontiers in Microbiology, 2021)
Honeybees (Apis mellifera) can be exposed via numerous potential pathways to ambient nanoparticles (NPs), including rare earth oxide (REO) NPs that are increasingly used and released into the environment. Gut microorganisms are pivotal in mediating honeybee health, but how REO NPs may affect honeybee health and gut microbiota remains poorly understood. To address this knowledge gap, honeybees were fed pollen and sucrose syrup containing 0, 1, 10, 100 and 1000 mg kg-1 of nano-La2O3 for 12 days. Nano-La2O3 exerted detrimental effects on honeybee physiology, as reflected by dose-dependent adverse effects of nano-La2O3 on survival, pollen consumption and body weight (P < 0.05). Nano-La2O3 caused the dysbiosis of honeybee gut bacterial communities, as evidenced by the change of gut bacterial community composition, the enrichment of pathogenic Serratia and Frischella, and the alteration of digestion-related taxa Bombella (P < 0.05). There were significant correlations between honeybee physiological parameters and the relative abundances of pathogenic Serratia and Frischella (P < 0.05), underscoring linkages between honeybee health and gut bacterial communities. Taken together, this study demonstrates that nano-La2O3 can cause detrimental effects on honeybee health, potentially by disordering gut bacterial communities. This study thus reveals a previously-overlooked effect of nano-La2O3 on the ecologically and economically important honeybee species Apis mellifera.